The Effect of Family and School Cultural Environment Through Self Efficacy on Student Learning Result - Ely Rizky Amaliyah; Heri Pratikto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
This study aims to explain the relationship between environmental variables out g a, school culture, self-efficacy and student learning outcomes Administrative Program Program at SMK. This research includes quantitative research type with the explanatory descriptive method. The sampling technique was proportionate stratified random sampling, the study sample consisted of 114 students. Data analysis in this research using path analysis. Results research shows that there is a positive and significant influence of family environment on self-efficacy, there is the positive and significant influence of school culture on self-efficacy, there is a direct positive and significant influence between the environment to the family on the results of learning. While the school culture The air does not directly influence the learning outcomes, but the air of self-efficacy ng driving direct effect on learning outcomes, and the family environment is not aired directly influence the outcome through self-efficacy jar arts students, and school culture has an indirect effect on learning outcomes through students' self-efficacy.